Cellular dissection of the spinal cord motor column by BAC transgenesis and gene trapping in zebrafish - Asakawa, Kazuhide; Abe, Gembu; Kawakami, Koichi (Frontiers in Neural Circuits, 2013)
Bacterial artificial chromosome (BAC) transgenesis and gene/enhancer trapping are effective approaches for identification of genetically defined neuronal populations in the central nervous system (CNS). Here, we applied these techniques to zebrafish (danio rerio) in order to obtain insights into the cellular architecture of the axial motor column in vertebrates. First, by using the BAC for the Mnx class homeodomain protein gene mnr2b/mnx2b, we established the mnGFF7 transgenic line expressing the Gal4FF transcriptional activator in a large part of the motor column. Single cell labelling of Gal4FF-expressing cells in the mnGFF7 line enabled a detailed investigation of the morphological characteristics of individual spinal motoneurons, as well as the overall organisation of the motor column in a spinal segment. Secondly, from a large-scale gene trap screen, we identified transgenic lines that marked discrete subpopulations of spinal motoneurons with Gal4FF. Molecular characterisation of these lines led to the identification of the ADAMTS3 gene, which encodes an evolutionarily conserved ADAMTS family of peptidases and is dynamically expressed in the ventral spinal cord. The transgenic fish established here, along with the identified gene, should facilitate an understanding of the cellular and molecular architecture of the spinal cord motor column and its connection to muscles in vertebrates.